2003
DOI: 10.2105/ajph.93.7.1089
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Femicide in Abusive Relationships: Results From a Multisite Case Control Study

Abstract: There are identifiable risk factors for intimate partner femicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
834
10
38

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,199 publications
(951 citation statements)
references
References 23 publications
32
834
10
38
Order By: Relevance
“…According to Campbell et al, chronic alcohol abuse does not represent a risk factor for femicide. 26 Belfrage and Rying, by contrast, observed that 44% of perpetrators and 37% of victims were under the effects of alcohol at the moment of the crime. 29 Belfrage and Rying also noted that the frequency of chronic alcohol abuse in femicide (51%), is generally lower than in other categories of homicide (61%) or in cases of aggression by the partner.…”
Section: Discussionmentioning
confidence: 95%
“…According to Campbell et al, chronic alcohol abuse does not represent a risk factor for femicide. 26 Belfrage and Rying, by contrast, observed that 44% of perpetrators and 37% of victims were under the effects of alcohol at the moment of the crime. 29 Belfrage and Rying also noted that the frequency of chronic alcohol abuse in femicide (51%), is generally lower than in other categories of homicide (61%) or in cases of aggression by the partner.…”
Section: Discussionmentioning
confidence: 95%
“…In Peru, estimates show that 8 of every 10 cases of sexual abuse are committed by a family member or acquaintance of the victim, and 6 of every 10 pregnancies among girls 11 to 14 are the result of incest or violence 26 . In the US, femicide is the seventh largest cause of premature death among young women (15 to 45), most of the time committed by partners or former partners 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more attention and protection are required for women who are the victims of violence by their partners, as this group is at the highest risk of death from their partners. Healthcare agents and professionals play a fundamental role in identifying and notifying cases of women attacked by partners or former partners 27 . It is important that investigation and counseling on intimate violence against women be part of routine OBGYN visits.…”
Section: Discussionmentioning
confidence: 99%
“…Mulheres que possuem melhores níveis de escolaridade, situação socioeconômica e laboral que os companheiros estão em maior risco 8,33 , indicando a presença do fenô-meno chamado backlash ou feminicidios perpetrados por homens (companheiros ou conhecidos) quando estão em situação socioeconômica ou social desvantajosa em relação às mulheres ou quando elas querem separar-se e eles não o desejam. Dentre os agressores há uma sobreprevalência de homens desempregados, que possuem armas de fogo, histórico de agressões e ameaças de morte dirigidas à vítima 8 .…”
Section: Cenáriosunclassified